A study on the TVET skills mismatch in Region X (Northern Mindanao Region) - Lobrido, Debra T.
The study was designed to confirm whether there exists a skills mismatch within the Northern Mindanao Region, specifically, in the labor demand and supply of skills by the TVET industry. Statistical figures like that of the gross value added income and the regions' level of investment, in addition to the major occupation and source of income by its workforce indicates that the region is primarily agricultural. For this, skills in the region should, in the same way be equipped in the said industry. Graduates produced by the TVET industry, however, did not meet such skills requirements; as such claim can be supported by the results from the correlation. Demand of skills as represented by the number of enrollees by the students, though were self- motivated, concentrates on non-agriculture related programs, and TVET providers responded to such demand. Meanwhile, since most of the private TVET providers were private ones and their courses offered were based on their head offices located somewhere outside the region, such factors contributed to the magnitude of skills mismatch in the region.